Bovine genome database: new curated collection of selective sweeps in bovine populations across the world - Kambal, Sumaya; Walsh, A.T.; Sivasankaran, S.K.; Adossa, Nigatu A.; Skarlupka, J.H.; Hanotte, Olivier H.; Suen, G.; Elsik, C.G. (Oxford University Press, 2026)
Mapping genome-wide selective sweeps is of high relevance in cattle population genomics, having successfully identified thousands of genomic regions and candidate genes, with potential to reveal links to agriculturally important traits such as those related to production and adaptation to extreme environments. However, pinpointing the underlying causal variants remains a key priority in understanding molecular mechanisms controlling these traits. The lack of an integrative resource for selective sweeps has impeded meta-analysis and candidate variant prioritization. In the current update of the Bovine Genome Database (BGD; https://bovinegenome.elsiklab.missouri.edu), we address this gap by incorporating a curated dataset consolidating 92 519 selective sweeps identified through 340 genome-wide analyses across 213 cattle populations worldwide. Incorporating this new dataset into BovineMine enables meta-analysis across studies and populations to identify consensus signals, and the exploration of selective sweeps in the context of genes, gene functions, genomic variations, and quantitative trait loci. Furthermore, the BGD JBrowse genome browser enables visualization of sweep regions alongside other genomic features and functional annotations such as histone marks, open chromatin regions, and chromatin states. This BGD update facilitates the prioritization of candidate causal variants and helps identify unanswered questions in disentangling the molecular basis of adaptive and economically important traits in cattle.